Better crop establishment, residue recycling and diversification for sustaining non-basmati rice (Oryza sativa) in western IGP - RADHESHYAM; JAT, SHANKAR LAL; PARIHAR, C M; JAT, M L; BIJARNIYA, DEEPAK; KUMAR, MANISH; PADHAN, SMRUTI RANJAN; JAT, H S (The Indian Journal of Agricultural Sciences, 2023)
The conventional non-basmati rice (Oryza sativa L.) is neither economical nor sustainable in IGP. Therefore, an on-farm study was carried out at the farmer’s field in Karnal district of Haryana to find out alternative by diversified crops having legume (summer mungbean) with the best tillage and residue management practices. The intensification through conservation agriculture (CA)-based crop management within the RW system (CTR–ZTWMb and DSR– ZTWMb) and beyond with diversification by maize (ZTMWMb and ZTMMuMb) gave statistically on par yield to conventional non-basmati rice (CTRW). Compared to CTRW, total water use was reduced by 0.8 and 14.8% in CTR– ZTWMb and DSR–ZTWMb, respectively. The total water use was significantly reduced by 53.9 to 60.8% with maize and soybean (ZTMWMb, ZTMMuMb, and ZTSWMb) over DSR–ZTWMb and CTRW. The net returns increased by ₹3.7–6.5 × 103/ha in CTR–ZTWMb and DSR–ZTWMb over the CTRW. In diversified systems, net returns increased by ₹10–16.5 × 103/ha with maize systems compared to three rice production scenarios. Similarly, in soybean, net returns enhanced by ₹4.6 × 103/ha over the CTRW systems. Moreover, there was a significant decrease in global warming potential (GWP) by 53.4–69.1, 53.3–69.0 and 46.9–64.8% was observed under ZTMWMb, ZTMMuMb and ZTSWMb, respectively over the three RW system treatments. These results demonstrate that crop diversification with the inclusion of maize and soybean with CA may be opted to improve crop and water productivity and farmer’s income replacing traditional rainy (kharif ) season non-basmati rice in Western Indo-Gangetic Plains (IGP).